2017
DOI: 10.1002/jobm.201700325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of virus‐derived siRNAs and their targets in RBSDV‐infected rice by deep sequencing

Abstract: RNA interference (RNAi) is a conserved mechanism against viruses in plants and animals. It is thought to inactivate the viral genome by producing virus-derived small interfering RNAs (vsiRNAs). Rice black-streaked dwarf virus (RBSDV) is transmitted to plants by the small brown planthopper (Laodelphax striatellus), and seriously threatens production of rice in East Asia, particularly Oryza sativa japonica subspecies. Through deep sequencing, genome-wide comparisons of RBSDV-derived vsiRNAs were made between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
6
13
1
Order By: Relevance
“…Consistent with previous report for diverse plant-virus-specific sRNAs (Donaire et al, 2008; Lan et al, 2018b; Xu and Zhou, 2017), CymMV and ORSV siRNAs also demonstrated a clear tendency to begin with uracil (U), adenine (A), as compared with cytosine (C) and guanidine (G) (Fig. 2E and F).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous report for diverse plant-virus-specific sRNAs (Donaire et al, 2008; Lan et al, 2018b; Xu and Zhou, 2017), CymMV and ORSV siRNAs also demonstrated a clear tendency to begin with uracil (U), adenine (A), as compared with cytosine (C) and guanidine (G) (Fig. 2E and F).…”
Section: Resultssupporting
confidence: 92%
“…In virus-infected sample, the majority (72% and 66%) of siRNAs derived from CymMV and ORSV were 18–22 nt in length, with 21 and 22-nt being most abundant (Fig. 2B and C); however, the majority of siRNAs in many virus-plant systems were 21–24 nt in length, with 21- and 22-nt being also most abundant (Kreuze et al, 2009; Lan et al, 2018b; Li et al, 2016; Mitter et al, 2013; Xu and Zhou, 2017; Yan et al, 2010; Yang et al, 2014). Thus, these results implicated that the homologues of DCL4 and DCL2 in P. equestris may be the predominant DCLs involved in the biogenesis of viral small interfering RNAs (vsiRNAs) which functions as the predominant antiviral silencing mediators (Blevins et al, 2006; Deleris et al, 2006; Ding, 2010; Donaire et al, 2008; Liu et al, 2018; Niu et al, 2017); as for other DCLs of P. equestris participating in vsiRNAs generation will be the future discussed topic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice cv. Nipponbare is known to be susceptible to RBSDV infection (Lan et al 2018), and rice cv. 15HPO187 was found to be resistant to RBSDV infection in our earlier field surveys.…”
Section: Introductionmentioning
confidence: 99%